IMPLEMENTASI KURIKULUM MERDEKA MELALUI MODEL PROJECT BASED LEARNING DI SEKOLAH DASAR - Ika Krisna Nurwiyati; Sigit Yulianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Online learning, demotivation and the use of technology bring problems in education. These conditions are also called learning loss, which appear in all levels of education and are getting worse due to the Covid-19 pandemic. The government issued the Independent Curriculum to reform the Indonesian education system. The Curriculum is the answer to learning loss problems. This research was conducted to explore the implementation of the Independent Curriculum through the Model Project Based Learning at the elementary level. Researcher explores the perspective of the school principal and the first grade’s teacher in implementing the Independent Curriculum through PjBL in class. This research uses a qualitative descriptive method with a case study approach. Researchers collected data through interviews, portfolios and analysis of related documents from the latest research. This research involved 1 principal and 1 first grade teacher at Bukit Aksara Elementary School, Semarang in the academic year of 2022-2023. To address learning loss, the school principal, as a policy maker, works in synergy with the teachers. Both parties have to get the same vision and mission that is aligned in understanding the independent curriculum, independent learning and how to implement the model PjBL. As a teacher develops resources and teaching skills on PjBL.